COMBINED STENOSIS OF ATHEROSCLEROSIS OF THE CORONARY AND RENAL ARTERIES - A PRACTICAL PROBLEM CARDIOLOGY - Abdullaev Ikrom Abduvalievich (Journal Park Publishing, 2023)
The prevalence of hemodynamically significant atherosclerotic lesions of the renal arteries (RA) among patients with severe coronary atherosclerosis ranges from 18.7 to 75.5%, and the mortality from complications in the combination of these diseases reaches 25-50%. Combined damage to the renal and coronary arteries (CA) worsens the prognosis for both the function of the heart muscle and the function of the kidneys, thereby affecting the progression of the disease. The relationship between vasorenal hypertension (VRH) of atherosclerotic origin and coronary heart disease (CHD) is still under discussion.